Editorial: What is GLASS? And what prospects does it open for sustainable urban development? - Kuzmin Evgeny; Suvorova Arina; Lavrikova Yulia; Sang Yanfang (E3S Web of Conferences, 2023)
Modern cities are encountering a large number of challenges from accelerating urbanization and population growth to increasing human impacts on the environment. To solve these challenging problems, an integrated approach is required. In the article, we introduce the GLASS (Green, Liveable, Amiable, Smart, Sustainable) system as such a comprehensive approach. Firstly, we describe each of the five components in the system, and analyse their interaction to create a progressive urban space. Then, we specify the content of the five components, clarify the limitations, assumptions and applicability of GLASS. We explain how green technologies (Green), favourable living conditions (Liveable), friendly social environment (Amiable), intelligent technologies (Smart) and sustainable practices (Sustainable) can jointly provide a higher quality of life for urban citizens. To show how the principles of GLASS can be integrated into urban planning practices and policies for sustainable urban development, we make an overview of the selected articles presented at the 7th International Regional Economics Conference (REC-2023) “Cities of New Age: GLASS”. The review of these publications provides insight into those aspects of GLASS that are currently being explored in modern cities research.